2013
DOI: 10.1021/bm4012562
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Stem Cell Adhesion and Morphology via Facile Control over Surface Presentation of Cell Adhesion Molecules

Abstract: ABSTRACT. To encourage cell adhesion on biomaterial surfaces in a more facile, safe, and lowcost fashion, we have demonstrated a non-covalent approach to spatially conjugate β-cyclodextrin (β-CD) modified peptide sequences onto self-assembled adamantane-terminated polystyrene-b-poly(ethylene oxide) (PS-PEO-Ada) films through inclusion complexing interactions between β-CDs and adamantane. By simply blending various ratios of unmodified PS-PEO with a newly synthesised PS-PEO-Ada, we produced PS polymer films tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…However, cell adhesion is mediated by non-specific physical interactions. Several studies have been published about adhesion mechanisms that affect cell morphology and adhesion-related signal transduction (Deligianni et al, 2001;Li et al, 2013;Yeung et al, 2005). In the current study, PS-MBP-FGF2 was used as an artificial substrate to control adhesion-mediated signalling and stem cell function through a specific receptor-ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cell adhesion is mediated by non-specific physical interactions. Several studies have been published about adhesion mechanisms that affect cell morphology and adhesion-related signal transduction (Deligianni et al, 2001;Li et al, 2013;Yeung et al, 2005). In the current study, PS-MBP-FGF2 was used as an artificial substrate to control adhesion-mediated signalling and stem cell function through a specific receptor-ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although hMSCs differentiate into osteoblasts under culture conditions in which their spread out shape is maintained, hMSCs that maintain a rounded morphology differentiate into adipocytes (McBeath et al, 2004). We reported that hASCs differentiate more readily into adipocytes than osteoblasts on surfaces with immobilised FGF2, suggesting that hASC differentiation is strongly correlated with the cell adhesion mechanism and that surfaces displaying immobilised FGF2 can serve as a unique artificial matrix for regulating integrin-mediated signalling and stem cell differentiation through FGF2-HSPG interactions (Kang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In concurrent work, the Cooper-White group used supramolecular interactions to display RGD in nanopatterned topographies produced by the segregation of Ad terminated polystyrene-co-PEO block copolymers (PS-PEO-Ad). 112 Such topographies are known to influence cell behaviors, including adhesion, spreading, and differentiation. [113][114][115] The ratio of PS-PEO/PS-PEO-Ad used to control the concentration of βCD-RGD bound within the nanodomains influenced cell adhesion and area.…”
Section: Cell-materials Interactionsmentioning
confidence: 99%
“…For example, a polystyrene-poly(ethylene oxide) (PS-PEO) copolymer system [39] was used to engineer a controlled cellular microenvironment for mesenchymal stem cells that contained nanodomains decorated with cell adhesion peptides [40]. We have produced surfaces where vertical cylinders of PEO in thin films of PS-PEO:PS mixtures on glass coverslips formed nanodomains [41] that were easily detectable as ~ 3 nm indentations with AFM (Fig 1A–1C, Figure A (B-C) in S1 File).…”
Section: Resultsmentioning
confidence: 99%